2014
DOI: 10.1002/nau.22601
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric fistula in a district hospital in DR Congo: Fistula still occur despite access to caesarean section

Abstract: VVF can occur after caesarean section because of the prolonged labor that already causes ischemia and necrosis of the bladder wall and vesicovaginal septum before or while the caesarean section is being performed. Access to general hospitals and the management of the pregnant women needs to be improved. Despite a reasonable closure rate of 65%, post-fistula incontinence remains an important clinical problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…In order to get more precise data on whether a fistula is truly iatrogenic Hilton [23] suggested to describe those fistulas as a "true obstetric or ischaemic fistula" where women who experienced obstructed labour, maybe sometimes for days, ultimately delivered a stillborn baby vaginally. He agrees with Raassen [25] as well as referrers to Onsrud [32] and Loposso [28] who describe that women who are delivered by CS of a live baby in a health facility after obstructed labour had been identified and who still develop a VVF "would be reasonably described as having an iatrogenic injury".…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In order to get more precise data on whether a fistula is truly iatrogenic Hilton [23] suggested to describe those fistulas as a "true obstetric or ischaemic fistula" where women who experienced obstructed labour, maybe sometimes for days, ultimately delivered a stillborn baby vaginally. He agrees with Raassen [25] as well as referrers to Onsrud [32] and Loposso [28] who describe that women who are delivered by CS of a live baby in a health facility after obstructed labour had been identified and who still develop a VVF "would be reasonably described as having an iatrogenic injury".…”
Section: Discussionsupporting
confidence: 53%
“…In his study the mean duration of labour among the fistula patients ranged from 2.5 to 4 days (60 to 92 h) [5]. In the DRC Loposso found in a collective of 146 women of whom 63.4% were delivered by CS that the mean duration of labour was 30.7 h [28]. 96 women (92.30%) of the 104 women treated at CCBRT for fistula in the investigated time period were delivered in a hospital either by a midwife (20.19%) or a doctor (70.19%).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…They consider these to be a distinct clinical (iatrogenic) entity and highlighted the training issues discussed above. Loposso et al similarly highlighted the risks of fistula in DRC despite the availability of caesarean section, but attributed this to the duration of obstructed labour prior to hospitalisation, and the delay in achieving caesarean delivery [ 33 ]. The various colleagues with whom the author has discussed this issue (see Acknowledgments), all with much greater experience of working in different low-income and middle-income countries in Africa and Asia, have given a range of views on the point.…”
Section: Post-caesarean Section Fistula: Traumatic or Ischaemic?mentioning
confidence: 99%
“…Low fistulae can also follow a successful cesarean section undertaken to relieve the obstruction, but after tissue necrosis in the lower vagina has occurred. Indeed, in a study of 146 women, Matthieu et al 8 reported that two-thirds of the women with a low obstetric fistula following prolonged labor had a cesarean section.…”
Section: Introductionmentioning
confidence: 99%